PHYSICAL AND BIOLOGICAL CHARACTERISTICS OF SOIL: A PERSPECTIVE STUDY - Gadekar, Deepak Janardhan; Santosh, Zine Aruna; Ramdas, Raut Vinod; Sonawane, Vinayak Vijay; Balu, Sumbare Popat (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Soil is also a natural resource, soil management is very important. Because soil fertility depends on three basic factors namely physical, chemical and biological. Because soil conservation is the need of the hour, it means that the quality of soil is decreasing due to many reasons like modern farming technology, chemical ingredients used in agriculture, contaminated water, various contaminated water from factories. We can see the effect of this on the agricultural production. Therefore, it is considered very important to study soil characteristics to maintain soil quality. Natural characteristics of soil are related to various factors such as crop growth, water drainage, moisture retention, plant nutrients. Also physical properties affect chemical and biological behavior. Although man-made causes are considered to be the most important factors behind the decline in soil fertility, studying soil characteristics is an important basis. For this reason, the above paper is being done from the point of view of making a theoretical study of soil characteristics. The information in this research paper is based on secondary data.